Pengaruh Profitabilitas, Likuiditas, Struktur Modal,Dan Financial Distress Terhadap Nilai Perusahaan Sebelum Dan Selama Pandemi Covid-19 (Studi Empiris pada Perusahaan Sub Sektor Restoran, Hotel, dan Pariwisata yang terdaftar di BEI Tahun 2018-2021) - Dewi, Kartika Candra; Vestari, Mekani (Magister Manajemen STIE Bank BPD Jateng, 2025)
The purpose of this study is to determine the effect of Profitability, Liquidity, Capital Structure, and FinancialDistress on Firm Value before and during the Covid-19 pandemic and to determine the difference inProfitability, Liquidity, Capital Structure, and Financial Distress on Firm Value before and during the Covid19pandemiconrestaurant,hotel,andtourismsub-sectorcompanieslistedontheIndonesiaStockExchangein 2018-2021.Thedatausedinthisstudyissecondarydataobtainedfromthefinancialstatementsofrestaurant, hotel,andtourismsub-sectorcompanieslistedontheIndonesiaStockExchangefor2018-2021.Theanalysis methodusedismultiplelinearregression.TheresultsofthisstudyshowthatProfitabilitybeforetheCovid-19 pandemichadanegativeinsignificanteffectonfirmvalue,whileProfitabilityduringtheCovid-19pandemic had a positive insignificant effect on firm value. Liquidity before the Covid-19 pandemic had a negativeinsignificant effect on firm value, while Liquidity during the Covid-19 pandemic had positive insignificant effecton firm value. Capital Structure before the Covid-19 pandemic had a significant positive effect on firm value,while Capital Structure during the Covid-19 pandemic had a significant positive effect on firm value. FinancialDistress before the Covid-19 pandemic had a significant positive effect on firm value, while Financial Distressduring the Covid-19 pandemic had a significant negative effect on firm value. There is no significant differencebetween firm value before and during the Covid-19 pandemic.